A novel solar desalination system based on an evacuated tube collective condenser heat pipe solar collector: A thermo-economic and environmental analysis - Nema, Garima; Karunamurthy, K (Frontiers in Mechanical Engineering, 2022)
Solar desalination has captivated consideration to overcome the problem of scarcity of fresh water, as simple design, economic, and environment-friendly solutions. This study navigates a novel solar evacuated glass tube collector integrated with a collective condenser heat pipe system for solar desalination. Anew designed heat pipe array was represented in this work by affixing all the evaporator tube units of heat pipes to a single condenser unit and was attached to the evacuated tube solar collector. The innovative assembly of the heat pipe provided uniform heating of water and rapid steam generation. The present system acts as a solar collector as well as a stand-alone basin for freshwater formation. The performance assessment of the neoteric system was conducted based on half-filled and three-fourths filled conditions of the water flow pipe kept within the collective condenser heat pipe. The maximum heat pipe temperature recorded during the half-filled state was 156.9 °C and 151.48 °C during the three-fourths filled state. The half-filled state of the water flow pipe delivered a total distilled water of 8050 ml/day whereas the three-fourths filled state delivered 5925 ml/day of distilled water. The maximum energy and exergy efficiency of the presented system was 19.27% and 3.92%, respectively. The economic minimum unit cost of freshwater by the present system is 4.27 INR and the payback period is 2.9 years. The present eco-friendly energy system saves 4.25 kWh of electricity and 4.16 × 10-3 tons of CO2 equivalent per year.